Relationships of Scincid Lizards (Mabuya spp; Reptilia: Scincidae) from the Cape Verde Islands based on mitochondrial and nuclear DNA sequences - Brehm, A. (2020)
Partial DNA sequences from two mitochondrial (mt) and one nuclear gene (cytochrome b, 12S rRNA, and C-mos) were used to estimate the phylogenetic relationships among the six extant species of skinks endemic to the Cape Verde Archipelago. The species form a monophyletic unit, indicating a single colonization of the islands, probably from West Africa. Mabuya vaillanti and M. delalandii are sister taxa, as indicated by morphological characters. Mabuya fogoensis and M. stangeri are closely related, but the former is probably paraphyletic. Mabuya spinalis and M. salensis are also probably paraphyletic. Within species, samples from separate islands always form monophyletic groups. Some colonization events can be hypothesized, which are in line with the age of the islands. C-mos variation is concordant with the topology derived from mtDNA.